METHODS FOR ASSESSING EDUCATIONAL OUTCOMES THROUGH CREATIVE PEDAGOGICAL APPROACHES: AN EMPIRICAL INVESTIGATION - Abdulkhayev Abduvokhid Abdulbori ugli (International Scientific and Current Research Conferences, 2025)
The effectiveness of creative pedagogical approaches in contemporary educational settings requires sophisticated assessment methodologies that extend beyond conventional standardized testing. This study examines multiple assessment methods designed to evaluate learning outcomes when creative teaching strategies are implemented. Through a comprehensive analysis of forty-three educational institutions employing creative pedagogical approaches including project-based learning, collaborative inquiry, and interdisciplinary problem-solving we evaluated the comparative efficacy of performance-based assessment, portfolio evaluation, peer assessment, and reflective practice documentation. Findings indicate that multimodal assessment frameworks combining quantitative and qualitative measures provide the most comprehensive evaluation of creative pedagogical effectiveness. Notably, authentic assessment methods demonstrate significantly stronger correlations with sustained learning retention and transfer capability than traditional achievement measures. This paper presents an integrated assessment framework applicable across educational contexts and grade levels.